Fiber characterisation of oil palm empty fruit bunch OPEFB)enzymme treatment and ultrasound treatment - Mahadevan, Deshan (2013)
Oil Palm Empty Fruit Bunch (OPEFB) is a major waste which is generously abundant in Malaysia.As the age of composite material is at hand,much effort has been put into research of new fiber based fillers for polymeric composite material. This research focuses on characterizing the abilities of laccase enzyme treated OPEFB with further ultrasound treatment to function as a fiber filler for polymeric materials.The end result is expected to show whether or not the modified fiber has an augmented property that could be used in application to further strengthen the structural properties of monolitich materials to become superior composites.Three particular methods of testing were chosen, which tensile test was using Universal Tensile Machine (UTM),lignin test to calculate the amount of removed lignin and water absorption test.At the end,it is clear that the usage of enzyme causes a severe fracture in the lingo-cellulosic backbone of the fiber and henceforth reduces certain aspects of its mechanical properties